Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA): A Tool for Employment Generation - Sami, Lamaan; Khan, Anas (International Journal of Social Sciences and Management, 2016)
This study is an empirical study which aims to examine the impact of MGNREGA in generating employment to poor in selected districts in India. Data have been collected through personal interview and analyzed with the application of linear regression. The analysis of the data revealed that MGNREGA played a significant role in generating employment, increase in income and consumption of respondents in selected districts in India. Int. J. Soc. Sc. Manage. Vol. 3, Issue-4: 281-286